Sociocultural approach of emotional involvement: The case of the Collective Uniting Hopes State of Mexico - Salazar-Gómez, Brayan A. (2024)
The violence in Mexico has brought a wide framework of complexities. According to the National Registry of Missing and Unaccounted For Persons (RNPDNO, 2024) “the State of Mexico, we are the third federal entity with the largest number of people whose whereabouts are unknown with 12,448, only behind Jalisco with 14,986 and Tamaulipas with 13, 176”. Faced with a bleak panorama, various organizational strategies have emerged that respond to the crisis of missing persons, as is the case of search collectives, which challenge the “status quo”. The objective of these for anthropology is vital, because they exposed the dynamics of resistance and power of collective social groups. The methodology corresponds to an ethnography of sensitive records, exploring in the digital platform “Collective Uniting Hopes State of Mexico”, the testimonial narratives of each participating member, in order to glimpse the political agencies that direct them to undertake their search actions. The results obtained show that emotions are the main agent that motivates the formation of search collectives, drives and strengthens cooperative relationships; the act of searching is in itself a political stance that responds to a systemic problem.